2011
DOI: 10.1177/0300985811424752
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Toxicity in a Group of Greyhounds Administered Ractopamine

Abstract: Ractopamine, a synthetic β(2)-adrenoceptor agonist, is widely used as a feed additive in the United States to promote a reduction in body fat and enhance muscle growth in cattle, pigs, and turkeys. It has the potential for illegal use in show and racing animals because it may affect performance via its β-adrenergic agonist properties or anabolic activities. Nine greyhounds were orally administered 1 mg/kg of ractopamine to investigate the ability to detect the drug in urine. Postdosing, 7 of 9 dogs developed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…With the increased use of internet sales, the internet has made this even banned product to be readily accessible for the aim of weight loss or dieting addition [2]. Ractopamine, a synthetic β2-adrenoceptor agonist, is now widely used as a feed additive in the United States to promote a reduction in body fat and to enhance muscle growth in cattle, pigs, or turkeys [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increased use of internet sales, the internet has made this even banned product to be readily accessible for the aim of weight loss or dieting addition [2]. Ractopamine, a synthetic β2-adrenoceptor agonist, is now widely used as a feed additive in the United States to promote a reduction in body fat and to enhance muscle growth in cattle, pigs, or turkeys [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at least the toxic effects on cardiovascular systems (such as tachycardia and hypertension) are considered to be of clinical relevance [7]–[9]. More recently, it was further reported that ractopamine administration might cause the myocardial toxicity in dogs [5].…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study in Greyhounds found that 7 out of 9 dogs administered ractopamine developed arrhythmias and elevations in cardiac troponin I (Yaeger et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…As a nonselective beta agonist, ractopamine has affinity for and efficacy at both the b1 (predominant in cardiac tissue) and b2 (predominant in muscle) receptor subtypes (Baker 2005); there is also evidence that ractopamine can interact with other receptors in vitro (trace amine-associated receptor 1, Liu et al 2014;estrogen receptor a, McRobb et al 2014). Acute myocardial toxicity has been reported in dogs following a single oral 1 mg/kg dose (Yaeger et al 2012). Acute myocardial toxicity has been reported in dogs following a single oral 1 mg/kg dose (Yaeger et al 2012).…”
Section: Introductionmentioning
confidence: 99%